PENERAPAN HYGIENE GRADE OLEH PEDAGANG TERHADAP INFEKSI PARASIT CRYPTOSPORIDIUM SP. (CRYPTOSPORIDIOSIS) - Nailah Zahrah Ardiningrum; Yauwan Tobing Lukiyono (Jurnal Ilmu Kesehatan Abdurrab, 2025)
Currently, there are still too many traders who do not pay attention to the health and even the safety of their buyers. So many studies relevant to this matter can be attributed to exposure to one of the intestinal parasites, namely Cryptosporidium sp. with the name of the disease is Crytosporidiosis. This disease is triggered by several things, one of which is the lack of implementation of hygiene grades in daily life and food processing patterns by food, beverage, or even snack traders. Unhealthy or even unsafe food or beverages can be characterized by exposure to or contamination from parasites, bacteria, chemical compounds, and even viruses that cause more than 200 diseases. Starting from food poisoning to diarrhea and even cancer. With the proper implementation of food sanitation, the implementation of hygiene grades properly, can minimize exposure to this parasite through food. Food Born Diseases are one of the biggest causes of parasite exposure in the world, because food processing patterns are sometimes not good and do not prioritize hygiene grade.